The hydrothermal alteration of the cordón de inacaliri volcanic complex in the framework of the hidden geothermal systems within the pabelloncito graben (Northern Chile) - Maza, Santiago Nicolás (2021)
Detailed mineralogical analyses in areas with surface hydrothermal alteration zones associated with recent volcanism (<1 Ma) in the Central Andean Volcanic Zone could provide key information to unravel the presence of hidden geothermal systems. In the Cordón de Inacaliri Volcanic Complex, a geothermal field with an estimated potential of ~1.08 MWe·km-2 has been recently discovered. In this work, we focus on the hydrothermal alteration zones and discharge products of this area, with the aim to reconstruct the geological processes responsible for the space-time evolution leading to the geothermal records. We identified (1) discharge products associated with acid fluids that could be related to: (i) acid-sulfate alteration with alunite + kaolinite + opal CT + anatase, indicating the presence of a steam-heated blanket with massive fine-grained silica (opal-CT), likely accumulated in mud pots where the intersection of the paleowater table with the surface occurred; (ii) argillic alteration with kaolinite + hematite + halloysite + smectite + I/S + illite in the surrounding of the acid-sulfate alteration; and (2) discharge products associated with neutral-alkaline fluids such as: (i) discontinuous pinnacle-like silica and silica deposits with laterally developed coarse stratification which, together with remaining microorganisms, emphasize a sinter deposit associated with alkaline/freshwater/brackish alkaline-chlorine water bodies and laterally associated with (ii) calcite + aragonite deriving from bicarbonate waters. The scarce presence of relics of sinter deposits, with high degree crystallinity phases and diatom remnants, in addition to alunite + kaolinite + opal CT + anatase assemblages, is consistent with a superimposition of a steam-heated environment to a previous sinter deposit. These characters are also a distinguishing feature of paleosurface deposits associated with the geothermal system of the Cordón de Inacaliri Volcanic Complex. The presence of diatoms in heated freshwater bodies at 5100 m a.s.l. in the Atacama Desert environment could be relatedwith the last documented deglaciation in the area (~20-10 ka), an important factor in the recharge of the hidden geothermal systems of the Pabelloncito graben.